Greenfield Gas Distribution : Cross-country Experience - World Bank (Washington, DC, 2014)
The study aims to present information about specific countries which have initiated gas distribution projects rather than suggestions. However, by drawing on the experience of a large number of countries, it also aims to provide practical lessons about issues which could potentially foster or impede gas distribution projects. The study emphasizes how countries vary in terms of the level of development of gas distribution networks. Chapter 3 outlines the major factors contributing to such diversity. These factors fall into three categories which form the basis for analyzing gas distribution in the countries selected in the study : supply-side factors, demand-side factors and policy choices of governments